Evaluation of the Ministry of Social Affairs Policy on Social Protection Programs in Indonesia - Rintia, Rintia; Sentosa, Ilham; Yudithia, Yudithia (Journal Governance Society, 2025)
This study evaluates the effectiveness of Indonesia's social protection policies, focusing on two key programs: Program Keluarga Harapan (PKH) and Bantuan Sosial Pangan (BSP). The research addresses the broader issue of poverty and social inequality in Indonesia, with particular attention to the challenges faced by vulnerable populations, including low-income families, the elderly, and people with disabilities. The study's purpose is to assess how well these social protection programs are achieving their intended outcomes of poverty alleviation and social inclusion. A qualitative research design was employed, utilizing secondary data from government reports, program evaluations, and relevant academic literature. The study analyzes the policy formulation, implementation, and evaluation processes of these programs through the lens of Dunn’s Circular Policy Evaluation Model, which emphasizes problem identification, policy formulation, implementation, and evaluation. The findings indicate that while PKH and BSP have contributed to immediate poverty relief and food security, they have not addressed the underlying structural causes of poverty, such as limited access to education and healthcare. The research concludes that although the programs provide significant short-term benefits, their long-term effectiveness is limited due to logistical challenges in program delivery and the failure to integrate broader development goals. The study suggests that future social protection strategies should focus on sustainable poverty reduction by addressing the root causes of inequality and improving service delivery mechanisms.